2018
DOI: 10.15403/jgld.2014.1121.271.pep
|View full text |Cite
|
Sign up to set email alerts
|

Pepsinogen Test for the Evaluation of Precancerous Changes in Gastric Mucosa: a Population-Based Study

Abstract: Aims: The aim of the study was to evaluate the rationale of blood pepsinogen (PG) testing in population based screening settings.Methods: Participants from a cross-sectional population-based study of cardiovascular risk factors in Latvia were invited to participate in the current study. Pepsinogen I and II were measured in blood samples taken during the initial study and at follow-up; upper gastrointestinal endoscopy was performed. There were three groups of patients: with moderately decreased (PG I< 70 ng/… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
15
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(17 citation statements)
references
References 39 publications
1
15
0
1
Order By: Relevance
“…Among the 38 studies for the diagnosis of GC, 28 studies [35,36,37,38,40,41,42,43,46,48,49,50,51,53,54,56,57,58,59,60,62,63,65,66,70,71,72,73] adopted the cut-off standard of PG I ≤70 ng/mL and PG I/PG II ratio ≤3, 11 studies [26,38,39,44,45,47,52,57,65,68,69] adopted the cut-off standard of PG I/PG II ratio ≤3, and only six studies [34,45,57,64,65,69] adopted the cut-off standard of PG I ≤70 ng/mL.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Among the 38 studies for the diagnosis of GC, 28 studies [35,36,37,38,40,41,42,43,46,48,49,50,51,53,54,56,57,58,59,60,62,63,65,66,70,71,72,73] adopted the cut-off standard of PG I ≤70 ng/mL and PG I/PG II ratio ≤3, 11 studies [26,38,39,44,45,47,52,57,65,68,69] adopted the cut-off standard of PG I/PG II ratio ≤3, and only six studies [34,45,57,64,65,69] adopted the cut-off standard of PG I ≤70 ng/mL.…”
Section: Resultsmentioning
confidence: 99%
“…From the 43 studies [21,26,27,34,35,36,37,38,39,40,41,42,43,44,45,46,47,48,49,50,51,52,53,54,55,56,57,58,59,60,61,62,63,64,65,66,67,68,69,70,71,72,73] for the diagnosis of gastric neoplasm, we identified a total of 114,448 patients (4689 patients with GC, 430 patients with neoplasm, 130 patients with dysplasia vs. 109,199 patients without gastric neoplasm). Among them, 20 [26,27,34,36,37,40,43,44,45,54,55,56,57,58,61,62,64,67,68,72] were case–control studies, whereas 18 [35,39,41,42,46,47,48,49,…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Sjomina et al in Latvia and Tepes et al in Slovenia also observed decreased PG 1/2 ratio in precancerous conditions of the stomach mucosa . Another study noted that the PG 1/2 ratio decreased with increasing age in a healthy Chinese population …”
Section: Noninvasive Testsmentioning
confidence: 84%
“…35 Sjomina et al in Latvia and Tepes et al in Slovenia also observed decreased PG 1/2 ratio in precancerous conditions of the stomach mucosa. 36,37 Another study noted that the PG 1/2 ratio decreased with increasing age in a healthy Chinese population. 38 Normal PG levels in obese patients (without "red flag" symptoms) may help in avoiding upper endoscopy before bariatric surgery.…”
Section: Other Biomarkers For H Pylori Detection or For The Evaluamentioning
confidence: 98%